Pressure pain mapping of equine distal joints: feasibility and reliability - Gisler, Jana; Chiavaccini, Ludovica; Blum, Severin; Montavon, Stéphane; Spadavecchia, Claudia (Frontiers in Pain Research, 2024)
Osteoarthritis is a prevalent degenerative joint disease initiating chronic pain and lameness in horses. While several objective gait analysis systems have been developed and validated to quantify lameness severity in horses, methods to evaluate whether peripheral sensitization contributes to the pain experienced are missing. Specific aims were to evaluate the feasibility and intra-and interrater reliability of pressure pain thresholds (PPT) determination at sites overlying the distal thoracic limb joints of clinically healthy horses. For feasibility assessment, PPT were measured with a hand-held digital algometer at six periarticular landmarks bilaterally on the distal thoracic limb of 40 healthy horses. The joints tested were the metacarpophalangeal, on the latero-palmar and dorsal aspects (L-MCP and D-MCP), the proximal interphalangeal, on the dorsal and palmar aspect (D-PIP and P-PIP) and the distal interphalangeal, on the dorsal and lateral aspect (D-DIP and L-DIP). For intra-and inter-rater reliability assessment, L-MCP and D-MCP were selected to be tested again at two weeks intervals in 20 out of the 40 horses. Data were analyzed using a mixed-effect linear model to test differences in threshold per site and limb. Intra-and inter-rater correlation was calculated. Bland-Altman plots were performed to evaluate the variability of the measures. The procedure was feasible in 95% of horses. Overall, median [interquartile range (IQR)] PPT was 9.4 (7.5-11.3)N. P-PIP and D-DIP recorded significantly lower PPT (p<0.001 and p=0.002, respectively) than L-MCP. Median (IQR) were 9.9 (7.3-12.4)N, 8.4 (6.1-10.5)N and 9.0 (7.4-10.6)N for L-MCP, P-PIP and D-DIP, respectively. The intra-rater agreement was 0.68 (95%CI 0.35-0.86) for L-MCP, and 0.50 (95%CI 0.08-0.76) for D-MCP. Inter-rater agreement was 0.85 (95%CI 0.66-0.94) for L-MCP and 0.81 (0.57, 0.92) for D-MCP. Evaluation of feasibility was performed only for distal thoracic limbs joints. Only warmblood and Freiberger horses were included. Intra-and inter-rater reliability assessments were performed exclusively on data collected at the MCP joint. Pressure pain mapping of distal thoracic limb joints was feasible in horses. Local sensitivity differed among sites and no side differences were noticed. Data collected from the MCP joint suggest highly variable, subject dependent intra-rater reliability, ranging from poor to good, and good to excellent inter-rater reliability.